2018
DOI: 10.1002/slct.201801416
|View full text |Cite
|
Sign up to set email alerts
|

Direct Ordering of Anchoring Events at the Surface of Iron Oxide Nanoparticles Enabled by A Stepwise Phase‐Transfer Strategy

Abstract: For most nanoparticle applications, understanding the "strength" of anchoring events at the surface is necessary to design effective ligand exchange processes. The present report demonstrates the ability to direct the ordering of phosphonic acid, catechol, and carboxylic acid as anchoring groups for iron oxide nanoparticles, enabled by a stepwise phase-transfer strategy. A key feature was the use of a cyclohexane-based thermomorphic system that provided a unique homogeneous field for ligand-exchange processes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The intensity of the signal increases with progressive functionalization. [47][48][49] In addition the IR spectra reveal the The C=O stretching vibration at 1637 cm -1 , which is present in all samples, shows a nonquantitative exchange of the oleic acid. The signal intensity suggests a significantly larger amount of remaining oleic acid compared to similar exchange protocols of DA and PEG phosphonic acid derivatives reported in literature.…”
Section: Synthesis Of the Cationic Organophosphorus Coupling Molecule Synthesis Was Carried Outmentioning
confidence: 86%
“…The intensity of the signal increases with progressive functionalization. [47][48][49] In addition the IR spectra reveal the The C=O stretching vibration at 1637 cm -1 , which is present in all samples, shows a nonquantitative exchange of the oleic acid. The signal intensity suggests a significantly larger amount of remaining oleic acid compared to similar exchange protocols of DA and PEG phosphonic acid derivatives reported in literature.…”
Section: Synthesis Of the Cationic Organophosphorus Coupling Molecule Synthesis Was Carried Outmentioning
confidence: 86%
“…Although carboxylates are categorized as tightly bound ligands by the use of colloidal NMR spectroscopy, they can quantitatively be exchanged by phosphonic acids, using CdSe, [11] PbSe, [12] and ZrO 2 [13] nanoparticles. Previously, we qualitatively demonstrated that carboxylates can be exchanged by phosphonic acids at Fe 3 O 4 nanoparticle surfaces by using a stepwise phase‐transfer strategy [14] . We questioned whether phosphonates tightly bound to nanoparticle surfaces can be exchanged by other phosphonic acids.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we qualitatively demonstrated that carboxylates can be exchanged by phosphonic acids at Fe 3 O 4 nanoparticle surfaces by using a stepwise phase-transfer strategy. [14] We questioned whether phosphonates tightly bound to nanoparticle surfaces can be exchanged by other phosphonic acids. Most colloidal NMR studies have used quantum dot nanoparticles as platforms, but the surface chemistry for metal oxide nanoparticles is somewhat less understood.…”
mentioning
confidence: 99%
“…Such a low binding affinity was highly unexpected, given many reports of successful surface functionalization with catechols. 39, 51, 54-58 However, in these reports water or biological buffers were used as the solvent. Therefore, we designed a competitive binding experiment directly in water.…”
Section: Resultsmentioning
confidence: 99%
“…38 Okada et al came to the same conclusion on 9 nm iron oxide NCs by performing phase-transfer experiments using polar and nonpolar phosphonic acids and catechols. 39 It is clear that despite the common usage of phosphonic acids and catechols in metal oxide NC functionalization, there is no clear consensus on the relative binding affinity. Furthermore, a direct link between ligand binding equilibria and the final colloidal stability of the NCs is usually not made.…”
Section: Introductionmentioning
confidence: 99%